Ramesside, Late Nubian and christian pottery from Serra West in the Museum of Natural History, La Plata - Fuscaldo, Perla (2011)
Fil: Fuscaldo, Perla. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina